(untitled) (Asian Business Research, 2018)
This research explores the phenomenon of firm performance as it relates to the business strategy, characteristics of Chinese Family Business (CFB) in Hong Kong’s Electronic Companies, and technology strategy adopted by these firms. The motive to do this research is that there has been very little work on business strategy in export-oriented "developing economies - latecomer economies" as referred by Zahra and Covin (1993). There has also been little work on technology policy/strategy in Hong Kong, although there have been many suggestions that Hong Kong firms "need" to change and up-grade their business strategies. Added to this, Hong Kong firms have interesting characteristics (Chinese Family Business, CFB), which may be related to their business and technology strategies. Performance may be determined by the strategies they adopt. In this research, the key dimensions of "technology strategy/policy" are identified, including Imitation, Original Equipment Manufacturing (OEM) and Original Design Manufacturing (ODM), which are important in Hong Kong, but which have not been explored much in the literature. Hong Kong firms were selected in this topic since as China is found to become the world’s manufacturing base and a lot of that industry, especially in Electronics Industry that this is an important topic.